Kamenev Type Oscillatory Criteria for Linear Conformable Fractional Differential Equations - Jing Shao; Zhaowen Zheng (Discrete Dynamics in Nature and Society)
Using integral average method and properties of conformable fractional derivative, new Kamenev type oscillation criteria are given firstly for conformable fractional differential equations, which improve known results in oscillation theory. Examples are also given to illustrate the effectiveness of the main results.